Study of a family of hybrid-Trefftz folded plate p-version elements - Jirousek, Jaroslav; Szybiński, Bogdan; Zieliński, Andrzej P. (Computer Assisted Methods in Engineering and Science, 2023)
The reported research presents a finite element formulation for folded plate analysis based on the p-version of the hybrid-Trefftz finite element model. The internal displacement field of the elements consists of a suitably truncated T-complete set of in-plane (u, v) and out-of-plane (w) components which satisfy the respective governing differential plane elasticity and thin plate (Kirchhoff) equations. Conformity is enforced in a weak, weighted residual sense through an auxiliary displacement frame, independently defined at the boundary of the element and consisting of displacement components u, v, w, wand normal rotation p = Wn. The displacement frame parameters are the global Cartesian displacements U, V, W at corner nodes and the hierarchical side-mode parameters for normal rotation and the global Cartesian displacement components, an optional number of which is allotted, formally, to mid-side nodes. The investigated approach is assessed on numerical examples.